Terompah panjang sebagai permainan tradisional dalam perspektif remaja Riau - Makorohim, M. Fransazeli; Yulianti, Mimi; Alficandra, Alficandra (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Terompah Panjang is a traditional game in Riau that needs attention. This study aims to analyze how to play and play equipment in the game. The method used is descriptive qualitative. Data were obtained by distributing questionnaires to adolescents in Riau by random sampling in the form of questions about the experience of playing the game Terompah Panjang. The sample was obtained based on teenagers who live and represent each region in Riau Province, as many as 65 teenagers. Data collection techniques through documentation techniques. Adolescents who are sampled meet the requirements as late teens (17-25 years) from the aspect of age and area of ​​residence, which are the general public. Data collection techniques through documentation techniques. Based on the study results, it was concluded that the perspective of Riau youth in the Terompah Panjang game was that this game did not have standard rules, both in the division of teams and the number of teams, and even the length of time from the track. The game is only based on an agreement in each area. Teenagers in Riau tend to play in their home environment, not at festivals organized by the local government or related agencies.